Optical fiber sensors: a route from University of Kent to Portugal - Santos, José L. (2011)
In this work the authors first summarily describe the main topics that were the subject of their post-graduate activity in fiber sensing at the Applied Optics Group of University of Kent in the late 1980s and early 1990s. After their return to Porto, Portugal, the know-how acquired during their stay at Kent and the collaboration paths that followed between the University of Porto and University of Kent were instrumental in the start-up and progress of optical fiber sensing activity in Portugal. The main topics addressed in this field, the description of some of the relevant developments achieved in recent years, the present situation and the guidelines for the future research and development activity in Portugal in fiber sensing will be the core of this work.